Вчення академіка М.М. Гришка про статевий поліморфізм конопель у світлі сучасної теорії генетичного контролю статі та досягнутого рівня однодомності - Міщенко, С.В.; Лайко, І.М.; Вировець, В.Г.; Кириченко, Г.І.; Кмець, І.Л.; Лайко, Г.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. Academician M.M. Hrishko doctrine of creation monoecious hemp forms and analysis of sexual structure of modern varieties are the aims of our study. Methods. The study was conducted in 2009–2015. Selfing of plants were held in a glass house. Individual insulators were used. Hemp sexual types were determined by the method M.D. Myhal. Plant nutrition area was 30 × 5 cm. Results. Ratio of sexual types of hemp modern varieties and first generation of inbred lines were established as a result of our research. Conclusions. Scientific achievements M.M. Hrishko were important for the further development of hemp genetics, breeding and hemp industry as a whole. High level of monoecious signs stability is characteristic of hemp modern varieties. Keywords: Cannabis sativa L., hemp, sex, monoecious, variety.